Mechanical stimulation of single cells by reversible host-guest interactions in 3D microscaffolds - Hippler, Marc; Weißenbruch, Kai; Richler, Kai; Lemma, Enrico D.; Nakahata, Masaki; Richter, Benjamin; Barner-Kowollik, Christopher; Takashima, Yoshinori; Harada, Akira; Blasco, Eva; Wegener, Martin; Tanaka, Motomu; et al. (Science advances, 2020)
Many essential cellular processes are regulated by mechanical properties of their microenvironment. Here, we introduce stimuli-responsive composite scaffolds fabricated by three-dimensional (3D) laser lithography to simultaneously stretch large numbers of single cells in tailored 3D microenvironments. The key material is a stimuli-responsive photoresist containing cross-links formed by noncovalent, directional interactions between.-cyclodextrin (host) and adamantane (guest). This allows reversible actuation under physiological conditions by application of soluble competitive guests. Cells adhering in these scaffolds build up initial traction forces of similar to 80 nN. After application of an equibiaxial stretch of up to 25%, cells remodel their actin cytoskeleton, double their traction forces, and equilibrate at a new dynamic set point within 30 min. When the stretch is released, traction forces gradually decrease until the initial set point is retrieved. Pharmacological inhibition or knockout of nonmuscle myosin 2A prevents these adjustments, suggesting that cellular tensional homeostasis strongly depends on functional myosin motors.
Gesehen am 08.12.2020